Structural Analysis and Conformational Dynamics of STN1 Gene Mutations Involved in Coat Plus Syndrome - Amir, Mohd.; Mohammad, Taj; Kumar, Vijay; Alajmi, Mohammed F.; Rehman, Md. Tabish; Hussain, Afzal; Alam, Perwez; Dohare, Ravins; Islam, Asimul; Ahmad, Faizan; Hassan, Md. Imtaiyaz (Frontiers in Molecular Biosciences, 2019)
The human CST complex (CTC1–STN1–TEN1) is associated with telomere functions including genome stability. We have systemically analyzed the sequence of STN and performed structure analysis to establish its association with the Coat Plus (CP) syndrome. Many deleterious non-synonymous SNPs have been identified and subjected for structure analysis to find their pathogenic association and aggregation propensity. A 100-ns all-atom molecular dynamics simulation of WT, R135T, and D157Y structures revealed significant conformational changes in the case of mutants. Changes in hydrogen bonds, secondary structure, and principal component analysis further support the structural basis of STN1 dysfunction in such mutations. Free energy landscape analysis revealed the presence of multiple energy minima, suggesting that R135T and D157Y mutations destabilize and alter the conformational dynamics of STN1 and thus may be associated with the CP syndrome. Our study provides a valuable direction to understand the molecular basis of CP syndrome and offer a newer therapeutics approach to address CP syndrome.